Comportamiento agronómico y productivo de la línea promisoria de arroz (Oryza sp.) L-37 en la zona de Vinces, provincia Los Ríos. - Solorzano Muñoz, Tommy Jim (2025)
Rice (Oryza sativa L.) is the most important crop for human consumption, second among cereals and a staple food for more than a third of the world's population. The main objective of this research was to determine the agronomic and productive performance of the promising rice line (Oryza sp.) L-37 in the Vinces area, Los Ríos province. The research was conducted on the "Mechita" farm, owned by Mr. Eduardo Benigno Carriel Ochoa, located on the Palizada Posa Seca road, Estero de Enemedio area, Vinces parish. The total population for both the promising line L-37 and INIAP 15 in R1, R2, R3 is 348 seedlings. Regarding the research design, a completely randomized design was used, including comparisons of means. For the analysis, three replicates (three samples with areas of 4 m² taken in one hectare of cultivation) and two cultivars (L-37 and INIAP-15) were considered. The results indicate that the promising line L-37 showed a better agronomic and productive performance compared to the INIAP-15 variety, with longer and thicker grains without husk, which resulted in a better grain yield in Vinces. The conclusions show that the agronomic characteristics tillers, panicles per plant, plant height, grains per panicle stood out in their results in the promising line L-37 and in relation to productive performance, the promising line L-37 reached a yield of 8558.33 kg/ha, surpassing the INIAP-15 variety that obtained 5850 kg/ha.